Inside the ROV control room onboard RV Celtic Explorer as part of research expedition: Advanced Mapping of Complex Marine Structures (2021). - Chris McGonigle:::Creator:::::::::::: (United Kingdom; Northern Ireland, 2023)
Technology in offshore operations. The view from inside the ROV control room onboard RV Celtic Explorer as part of research expedition: Advanced Mapping of Complex Marine Structures. Photograph and article "None of it is important or all of it is: Steinbeck, Ricketts, Ecology, and Identity," appear in Steinbeck Review, vol.16, no.2, 2022.